(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
The prepyloric diaphragm (A type of pyloric atresia) is a rare type of congenital malformation of gastrointestinal tract of unknown etiology. A thin two layered mucus membrane of about 2 to 4 mm, proximal to pylorus causes the gastric outlet obstruction in neonate. We are reporting a case of prepyloric diaphragm which had been diagnosed at 37 weeks of gestation by Ultrasonography and diagnosis was confirmed after birth during surgery. Prenatal ultrasonography of a 37 weeks pregnant mother revealed polyhydramnios, persistently dilated, a fluid filled blind sac at epigastrium and right hypochondrium with peristaltic wave and to & fro movements of fluid contents. There was no double bubble sign. The baby boy was born by Caesarean Section. After breast feeding, baby had non-bilious vomiting with mild abdominal distension. Postnatal ultrasonography showed dilated fluid filled stomach. Exploratory laparotomy on 14thday of life revealed a prepyloric diaphragm with a central hole, 1 cm proximal to the pylorus. The 2 mm thick diaphragm was excised circumferentially. Postoperative period was uneventful. Milk feeding started at 6th post-operative day and discharged with advice at 7th post-operative day. Prepyloric diaphragm or antral web is to be considered as provisional diagnosis if there is prenatal suspicion of gastric outlet obstruction, polyhydramnios of mother and persistent non-bilious vomiting in neonate; as simple excision of the diaphragm is curative for this unusual abnormality if there is no other associated abnormality. Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 67-69